Evaluating Types of TAPVR on Echocardiography and CT Angiography in Paediatric Patients Admitted in Tertiary Care Hospital: A Comparative Study - Rumana Sangi, Aliya Kemal Ahsan, Parveen Akhtar, Abdul Sattar Shaikh, Saba Mumtaz, Nazish Alisher, Amber Kamran, Musarat Nazir Sandano (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the types of TAPVR on Echocardiography and CT Angiography in Paediatric Patients Study design: A comparative study Place and Duration: Pediatric cardiology department and CT Angiography department of the National Institute of Cardiovascular Diseases (NICVD) Karachi from January 2019 to December 2021 Methodology: Patients who have TAPVR confirmed by CT angiography and detected by echocardiography were included in the research. Cases having anomalies in the systemic veins were eliminated. Demographic variables (age, gender, weight, etc.), echocardiographic results (such as type of TAPVR, obstructive and non-obstructive), and CT angiography findings were collected for the study using a preset structured proforma. We evaluated the diagnostic disparity between the two modalities. Results: In the present study there were 107 patients, 67.3% were male gender, 56.1% with age less than 6 months, the median age was 6 months, median weight was 4.5 kg. On echocardiography, there were 83.2% non-obstructive, 47.7% supracardiac and 36.4% cardiac TAPVR. On CT angiography, there were 66.4% were non-obstructive, 53.3% supracardiac and 23.4% cardiac TAPVR. Of the associated cardiac diseases, in common 86.9% were found with atrial septal defect, 13.1% were persistent left superior vena cava, 12.1% were patent ductus arteriosus, 8.4% were a ventricular septal defect, 6.5% were of pulmonary atresia, and 3.7% were complete endocardial cushion defect. Conclusion: As compared to echocardiography, CT angiography is more reliable for the detection of obstructive and mixed types of TAPVR. Detection of the supracardiac type of TAPVR is also almost the same as on echocardiography and CT angiography. As compared to CT angiography, echocardiography over diagnoses the non-obstructive type of TAPVR. CT angiogram is also useful in detecting other associated lesions such as heterotaxy, abnormal coronaries, presence of bilateral superior vena cava and coronary sinus. Keywords: TAVPR, echocardiography, CT angiography, cardiac disorders